Sustainable care: How CSR shapes wellbeing in healthcare organizations in Beijing, Shanghai, and Guangzhou. - Qinghua Fu; Belal Mahmoud AlWadi; Matac Liviu Marian; Rui Dias (PLoS ONE)
This article investigates the link between corporate social responsibility (CSR) perceptions of employees and employee burnout, from a sustainable development point of view, in the healthcare system of China. It fills the void in conventional literature by analyzing the indirect effect of CSR on the health and well-being of health workers aligning with SDGs focused on health and wellbeing. To be able to address the crux of healthcare professionals' burnout which can have far-reaching negative consequences for individual welfare and healthcare delivery, this research explores the linkages between CSR perceptions, employee burnout, happiness, psychological safety, and altruistic behavior. Data were obtained from 392 health care workers in three Chinese cities through a thrice-administered questionnaire that measures CSR perceptions of employees, burnout levels, happiness, safety perceptions, and altruistic motivations. It is seen that results show a strong link between CSR perceptions of employees and burnout reduction. Furthermore, the happiness and psychological safety of workers were expressed as mediators, with altruism playing the role of moderator. The above points highlight the need to adopt CSR strategies to promote employee well-being and combat burnout in the healthcare sector, which plays a vital role in global initiatives to attain SDGs related to good health and well-being, and sustainable development. Additionally, this research increases the debate on employee burnout based on their organization's CSR perceptions and positive psychology theory as a lens, bringing up CSR as the key factor in the achievement of sustainable development and the improvement of well-being within healthcare settings.